Analysis of Obstacles and Solutions to the Implementation of the Merdeka Curriculum in the Context of Vocational High Schools - Abriawan Bambi, Ade; Nasir, Nasir; Fachrunnisa, Fachrunnisa; Yuni Syam, Asthuty; Najir, Muhammad; Pujiyati, Wresni; Fatmawati, Titi; Mujiati, Mujiati; Anggraeni, Ageng (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2026)
The implementation of the Merdeka Curriculum at vocational high schools in Kendari City faces various systemic and structural barriers that significantly impact the effectiveness of teaching and learning. This study aims to identify the real challenges in the implementation of the Merdeka Curriculum and to offer contextual strategies based on empirical findings. This study used a qualitative approach and data collection technique by in-depth interviews. The informants consisted of principals, vice principals for curriculum, and teachers from seven vocational high schools in Kendari City. Data analysis was conducted using thematic analysis techniques, covering three main stages: data reduction, data presentation, and conclusion drawing. The findings revealed that the main challenges include the high administrative workload for teachers, limited training and technical assistance, inadequate facilities and infrastructure, unequal utilization of technology, disparities in teachers’ understanding, the absence of evaluation guidelines for productive subjects, cultural barriers in reflective practices, and limited time to conduct authentic assessments. These barriers lead to ineffective learning processes, inconsistency in evaluation standards across classes, and suboptimal implementation of authentic assessment in line with the philosophy of the Merdeka Curriculum. Based on these findings, this study recommends contextual strategies through teacher capacity strengthening, provision of adequate infrastructure, enhancement of technical support, development of contextual evaluation guidelines for vocational schools, and the establishment of a reflective and collaborative evaluation culture in schools. The success of implementation of the Merdeka Curriculum in Kendari City vocational schools largely depends on the synergy of policy, resource support, and the transformation of the school work culture.